Possible protective effects of two different doses of cyanocobalamin against methotrexate nephrotoxicity in rats - Alduboni, Noor Mohammed; N Al-Shawi, Nada (Iraqi Journal of Pharmaceutical Sciences, 2022)
Abstract Nephrotoxicity is defined as rapid deterioration in kidney functions. It arises from direct exposure to drugs or their metabolites. Methotrexate is a famous chemotherapeutic drug with anti-inflammatory and immunosuppressive properties. A high-dose methotrexate-induced renal dysfunction can be life threatening. Cyanocobalamin, one of the forms of vitamin B12, acts as a coenzyme in the conversion of homocysteine to methionine in the cytosol, and the conversion of methylmalonyl-CoA to succinyl-CoA in the mitochondrion. This study is designed to examine the effect of cyanocobalamin in two different doses each co-administered with methotrexate at 20 mg/kg induced nephrotoxicity in rats through the involvement of Nrf2/keap1 molecular mechanism in this respect. Rats utilized in this study were randomized into 4 groups (ten rats per each group); Group 1- (Control) rats intraperitoneally injected with 0.5ml normal saline once daily for 7 consecutive days. Group 2- Rats intraperitoneally injected with 0.5ml normal saline once daily for 7 consecutive days; and at day 2, a single intraperitoneal dose of methotrexate (20mg/kg) is to be injected. Group 3- Rats intraperitoneally injected with a 0.5mg/kg cyanocobalamin once daily for 7 consecutive days, and at day 2, a single intraperitoneal dose of methotrexate (20mg/kg). Group 4- Rats intraperitoneally injected with a 2mg/kg cyanocobalamin once daily for 7 consecutive days, and at day 2, a single intraperitoneal dose of methotrexate (20mg/kg). Co-administration of cyanocobalamin at doses cyanocobalamin 0.5mg/kg and 2mg/kg with methotrexate showed significant reduction (P<0.05) in malondialdehyde, significant elevation (P<0.05) in reduced glutathione level, significant upregulation in renal Nrf2 expression and significant down regulation in renal keap1 expression each compared to corresponding levels in methotrexate-only treated group. In conclusion this study demonstrated that co-administration of cyanocobalamin at two different doses with MTX resulted in attenuation of its nephrotoxicity by the utilization of selected parameters.Keywords: Nephrotoxicity, methotrexate, cyanocobalamin, malondialdehyde, glutathione, Nrf2, Keap1.